Premises, practices and politics of co-creation for urban sustainability transitions - Collier, Marcus (My University, 2025)
Co-creation is becoming a widely used mode of urban governance and research for city- making and city-transitioning being conceptually entangled with experimentation, innovation and collaboration. In this paper, we address three questions to systematize knowledge about and advancing the research and practice of co-creation: Why co-create? How to co-create? With whom to co-create? We first present three distinct premises of co-creation that respond to the question of why to co-create, and mark advantages of co-creation in comparison to participatory processes: bridging and weaving knowledge for place-based urban transitions, emancipating urban policy and planning, and advanc- ing research to transformative and transdisciplinary approaches that are socially relevant. We then present key practices and skills required for engaging in and organizing co- creation processes (i.e., how to co-create). Next to advocacy, communication, leadership, and organizational skills, we identify that creativity, playfulness, emotional intelligence, receptivity, and collaborative learning are important, yet often overlooked, skills and capabilities for co-creation. Finally, we investigate the politics of co-creation through the lens who is included in co-creation and how (i.e., with whom to co-create). We discuss future research on co-creation and its applications centered on measuring its impact against its premises while recognizing the importance of having different metrics and reflexive measures that can evaluate its deep impact and its relation to urban transitions.
Keywords: Co-creation, Urban governance, Transdisciplinary research, Transitions, Knowledge, Policy; Identities in Transformation; Smart & Sustainable Planet; Environmental planning and sustainable development; NATURE-BASED SOLUTIONS; Nature-based enterprise; SUSTAINABLE COMMUNITIES; Sustainable Development; Sustainable Urbanism; Sustainable innovation; Sustainable service development and innovation; TRANSITIONS; co-creation; resilience; Community; Development; Environment and housing; Policy; Social exclusion; Social participation